2011
DOI: 10.1109/lawp.2012.2183631
|View full text |Cite
|
Sign up to set email alerts
|

Metasurfing: Addressing Waves on Impenetrable Metasurfaces

Abstract: Metasurfaces constitute a class of thin metamaterials, which are used from microwave to optical frequencies to create new antennas and microwave devices. Here, we propose the use of variable-impedance metasurfaces for transforming surface or guided waves into different wavefield configurations with desirable properties. We will shortly refer to this metasurface-driven wavefield transformation as "metasurfing." Metasurfing can be obtained by an appropriate synthesis of inhomogeneous metasurface reactance that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
177
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(180 citation statements)
references
References 16 publications
0
177
0
Order By: Relevance
“…At microwave frequencies, impenetrable metasurfaces are realized as a dense periodic texture of small elements printed on a grounded slab. A penetrable metasurface (called metasheet) involves a periodic planar distribution of small elements placed on a very thin host medium penetrable for electromagnetic waves [39][40][41][42].…”
Section: Metasurfaces and Metasheetsmentioning
confidence: 99%
“…At microwave frequencies, impenetrable metasurfaces are realized as a dense periodic texture of small elements printed on a grounded slab. A penetrable metasurface (called metasheet) involves a periodic planar distribution of small elements placed on a very thin host medium penetrable for electromagnetic waves [39][40][41][42].…”
Section: Metasurfaces and Metasheetsmentioning
confidence: 99%
“…Since the elements are subwavelength in dimension, they can be used to approximate continuous hologram solutions, such as that considered early on by Oliner and Hessel [18]. The surface-wave metasurface antenna has proven to be an attractive platform for electrically large and conformal apertures [19], with many antenna variations now demonstrated [20][21][22][23][24][25]. The concept of slot arrays has also gained traction as a means of enabling beam synthesis for different applications [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The surface impedance is a continuous function in [18], so that there is no reduction to implementation in this work. That reduction to realizable structures occurred later [17,19,20] in the context of launching a surface mode that would then radiate as a collimated beam. This is an inherently different type of analysis and structure, and one that depending on a discrete surface impedance that would closely approximate a smooth, continuous function.…”
Section: Introductionmentioning
confidence: 99%
“…However, Pendry et al 8 showed theoretically, and experiment has since confirmed 9 that subwavelength surface structure (i.e. a metasurface 10 ) can bind the mode to the interface, leading to surface-plasmon-like behavior, even on perfect conductors. These metasurfaces have found applications such as antenna design at microwave frequencies.…”
mentioning
confidence: 99%
“…These metasurfaces have found applications such as antenna design at microwave frequencies. 10,11 One such example of a structure that supports TM surface waves is the Sievenpiper "mushroom" array; 12 a very thin metasurface that provides the necessary boundary condition to support a TM surface wave. 13 The lowest order resonance of this surface acts as a limit frequency to the TM surface wave, in the same way that the waveguide cutoff of Pendry's original hole array 8 provided a dispersion of the surface-plasmon form.…”
mentioning
confidence: 99%